Bagaimana Miskonsepsi Matematika terjadi pada materi Operasi Bilangan Bulat Dan Pecahan :? - Rudi Dwi Pramono; Mustafa Kamal; Muhammad Zul Hazril (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study aims to determine the misconceptions of high school students in basic arithmetic operations as measured by number sense. Number Sense is a form of intelligence in which students are sensitive to the relationship between the numbers they see and the material that these students understand. This research involved 76 participants from class X at SMAN 83 Jakarta consisting of 60 science students and 16 social studies students. The research method used is qualitative by collecting data using a questionnaire. The research results show that the average student (50% of the respondents) has misconceptions in solving problems in the form of stories. Students are unable to apply arithmetic operations correctly if the questions are changed in story form (28%). Students cannot represent a value in another form (38%). Students also experience mistakes in performing multiplication and division operations (12%). On average students can sort numbers in the form of fractions and decimals (55%) and students can solve problems that are applied in everyday life (57%). The confusion experienced by students when viewed from their majors did not differ much in answering correctly (IPA 38%, IPS 36%) or answering incorrectly (IPA 62%, IPS 64%). Â Penelitian ini bertujuan untuk mengetahui miskonsepsi siswa sekolah menengah atas dalam operasi hitung dasar yang diukur menurut number sense. Number Sense merupakan suatu bentuk kecerdasan di mana siswa peka terhadap hubungan antara angka yang siswa lihat dengan materi yang dipahami oleh siswa tersebut. Penelitian ini melibatkan 76 partisipan dari kelas X di SMAN 83 jakarta yang terdiri dari 60 siswa IPA dan 16 siswa IPS. Metode penelitian yang digunakan adalah kualitatif dengan pengumpulan data menggunakan kuisioner. Hasinl penelitian menunjukan bahwa rata-rata siswa (50% dari responden) memiliki miskonsepsi dalam penyelesaian masalah dalam bentuk cerita. Siswa tidak mampu mengaplikasikan operasi hitung dengan benar jika soal diubah dalam bentuk cerita (28%). Siswa tidak dapat merepresentasikan suatu nilai dalam bentuk lain (38%). Siswa juga mengalami kekeliruan dalam melakukan operasi perkalian dan pembagian (12%). Rata-rata siswa dapat mengurutkan bilangan dalam bentuk pecahan dan desimal (55%) dan siswa dapat menyelesaikan masalah yang diaplikasikan dalam kehidupan sehari-hari (57%). Kekeliruan yang dialami oleh siswa jika ditinjau dari jurusannya tidak berbeda jauh dalam menjawab benar (IPA 38%, IPS 36%) atau menjawab salah (IPA 62%, IPS 64%).